Recognition and importance of scientific training programs in the formation and preparation of youth handball teams: a field study of the Regional Association of Constantine - Sedira, saad (sports creativity, 2025)
Training programs play a significant and sensitive role in the development of players, especially younger ones, as they are the means through which players can acquire the physical, technical, mental, and psychological abilities that contribute to raising their level to the highest degree. The coach is the core and center of the training process and is responsible for implementing it to achieve the best possible results. If there is no qualified coach who is familiar with the content of the training process, the effort, money, and time invested will not yield the desired training results. The coach must be a leader who understands the training programs. Anyone observing Algerian handball will notice from the outset a lack of clear objectives, both at the ideological level and at the practical level, in the preparation and training of youth players. This research aims to identify the objectives of sports clubs in terms of preparing and training young handball players and to reveal the reasons for the failure of sports clubs to achieve their objectives with regard to young players.